Regional shifts in production and trade in the metal markets: a comparison of China, the EU, and the US - Johannes Perger (Mineral Economics, 2022)
Metal raw materials are essential for industrial production. Global metal markets have changed considerably since the start of the twenty-first century, China being the most influential driver of this change. With China's economic rise, metal demand has skyrocketed, and global production shares in metal raw materials and trade volumes have shifted towards the People's Republic. While China has become the dominant location for global metal production and consumption, older industrial economies like the European countries or the US have lost global share. This paper aims to compare the different developments in China, the European Union and the US regarding markets for the base metals aluminium, copper, lead, nickel, tin and zinc as well as iron and steel. The analysis covers movements in industrial production, metal production locations (mining – refined production – refined consumption) and metal trade volumes (ores and concentrates – waste and scrap – refined products and articles thereof).
Keywords: 660; Base metals; Processing; Trade; Asia; Europe; North America